2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--23036
|View full text |Cite
|
Sign up to set email alerts
|

STEM Summer Institute Increases Student and Parent Understanding of Engineering

Abstract: began as the Director of the Center for STEM Education in April 2011 just as the Center began. An engineer by training and in her ways of thinking, she received a BSE in biomedical and electrical engineering from Duke University in 1991. She then earned her M.S. from Drexel University in 1993 and her Ph.D. in biomedical engineering from Vanderbilt University in 1996. Dr. Klein-Gardner's career focuses on K-12 science, technology, engineering and mathematics (STEM) education, particularly as it relates to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It has been reported that positive effects were detected in the theme of "The effect of family participation in the STEM program (parent-child activities)", which was the most studied among the determined themes (Ata-Aktürk and Demircan, 2021;De Leon and Westerlund, 2021;Klein-Gardner, 2014;Kruchten and O'Malley, 2016;Pagano et al, 2020;Respres et al, 2022;Sheahan, 2016;. Family Science and Math Days/Nights had been the subject of many studies (De Leon and Westerlund, 2021; Kaya and Lundeen, 2010;Landerholm et al, 1994;Milner-Bolotin and Milner, 2017;Respres et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that positive effects were detected in the theme of "The effect of family participation in the STEM program (parent-child activities)", which was the most studied among the determined themes (Ata-Aktürk and Demircan, 2021;De Leon and Westerlund, 2021;Klein-Gardner, 2014;Kruchten and O'Malley, 2016;Pagano et al, 2020;Respres et al, 2022;Sheahan, 2016;. Family Science and Math Days/Nights had been the subject of many studies (De Leon and Westerlund, 2021; Kaya and Lundeen, 2010;Landerholm et al, 1994;Milner-Bolotin and Milner, 2017;Respres et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Technology-based activities have produced important results especially in terms of providing parent-child conversation (Pagano et al, 2020;. With family involvement engineering activities are also programs that have positive effects for STEM education (Ata-Aktürk and Demircan, 2021;Klein-Gardner, 2014;Pagano et al, 2020). Klein-Gardner (2014) showed that parents who participated in homework and engineering project presentations through the STEM summer institute program increased their daughters' desire to enter an engineering career.…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that parents are important models in children's decision making regarding career and life aspirations [1,[5][6][7][8]. Many studies have shown that parental involvement and parental expectations help students to have greater ambition for school success and career development [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it is critical that parents have the necessary knowledge and understanding of STEM areas; in the case of this work specifically, engineers and engineering. Parents who have accurate knowledge and understanding of engineers and engineering will be able to introduce their children to these areas early and guide their children to consider STEM fields in general, and engineering specifically, as good fields for their future careers [7].…”
Section: Introductionmentioning
confidence: 99%
“…And teaching subjects like engineering that had very limited resources became the least of parents' priority, if not eliminated completely. Thus, in an effort to help parents with young children, by using resources previously published [6][7][8][9] and to expand engineering education resources for parents, we planned a series of workshops for parents to help teach their kids engineering using everyday items. Previous studies have…”
Section: Introductionmentioning
confidence: 99%